Improvement of Power System Stability by using SVC with Cascade PID Controller (Global Journals of Research in Engineering, 2013)
In power system one most crucial problem is maintaining system stability The main reasons for occurring stability problem in the system is due to the fault occurs in the system In this paper the effect of SVC on voltage stability is investigates using cascade Proportional Integral Differential controller SVC is a shunt type FACTS device which is used in power system primarily for the purpose of voltage and reactive power control The cascade PID controller parameters has been selected by using Tyreus-Luyben settings method for primary loop controller and modified Ziegler-Nichols method for secondary loop controller Cascade control is mainly used to achieve fast rejection of disturbance before it propagates to the other parts of the plant PID controller in cascade architecture is the best choice compared to conventional single loop control system for controlling nonlinear processs The primary controller is used to calculate the setpoint for the secondrary controller The effect of fault on line with SVC and SVC with supplementary controller is also investigates In this paper A power system network is considered which is simulated in the phasor simulation method the network is simulated in three steps without SVC With SVC but no externally controlled SVC with cascade PID The result of the Simulation shows that SVC with cascade PID controllers are more effective to enhance the voltage stability and increases power transmission capacity of a power system The power system oscillations is also reduced with controllers in compared to that of without controllers So with cascade PID controllers the system performance is greatly enhanced
Keywords: svc; voltage regulator; cascade propotional integral differential controller; matlab simulink